Investment design from engineering management point of view - a case study for manufacturing industry - Şengün, Bilge Kağan (My University, 1993)
unknown
Keywords: Genel yönetim; Mali yönetim; Organizasyon ve finansman; SANAYİ-; STRATEJİK YÖNETİM